Reframing Regulation: ‘Privatisation’, De-democratisation and the End of Social Protection? - Steve Tombs (Revue Française de Civilisation Britannique)
This paper considers how the re-framing of regulation, in ways that have allowed an inter-penetration of private sector mentalities and actors with state regulators, have combined in the UK to produce both a de-democratisation and the erosion of social protection. It does so through an exploration of the enforcement of law designed to regulate business. In particular, I examine enforcement and regulatory policy at Local Authority level under the guise of the Better Regulation initiative and, then, conditions of austerity. These contexts have produced the opportunities for reframed – that is, specifically, marketised – forms of regulation which prioritise the interests of business over social protection. The paper also argues that they have been crucial in producing conditions whereby the fire at Grenfell Tower must be partly understood – conditions of de-democratisation and the decline of social protection.